2011
DOI: 10.1080/10494820903520040
|View full text |Cite
|
Sign up to set email alerts
|

Programming-languages as a conceptual framework for teaching mathematics

Abstract: Formal mathematical methods remain, for most high school students, mysterious, artificial and not a part of their regular intuitive thinking. The authors develop some themes that could lead to a radically new approach. According to this thesis, the teaching of programming languages as a regular part of academic progress can contribute effectively to reduce formal barriers. This education can also be used to enable pupils to access an accurate understanding of some key mathematical concepts. In the field of heu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(42 citation statements)
references
References 3 publications
0
38
0
4
Order By: Relevance
“…Early research also highlighted the potential of expressing mathematical ideas as computer programs (Feurzeig et al 1969;Hatfield and Kieren 1972). Noss and Hoyles (1996, pg.…”
Section: History Of Programming and Mathematics Learning For Childrenmentioning
confidence: 99%
“…Early research also highlighted the potential of expressing mathematical ideas as computer programs (Feurzeig et al 1969;Hatfield and Kieren 1972). Noss and Hoyles (1996, pg.…”
Section: History Of Programming and Mathematics Learning For Childrenmentioning
confidence: 99%
“…The idea that young learners should be taught to program, and that doing so has far reaching benefits, originated with the Logo Project [4], [5]. Papert found that "when a child learns to program, the process of learning is transformed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Logo was designed explicitly to teach mathematics, and many researchers have studied it as a vehicle for algebra (e.g., [5,6]). Pea and Kurland [9] found no evidence of improved mathematical reasoning among students who had been exposed to more than 30 hours of instruction in Logo, and later questioned the entire expectation of transfer into algebra.…”
Section: Related Workmentioning
confidence: 99%